PEGylated liposome IHL-305 markedly improved the survival of ovarian cancer peritoneal metastasis in mouse - Konishi, Hiroaki (BioMed Central, 2012)
BACKGROUND: Advanced ovarian cancer is characterized by peritoneal metastasis and the accumulation of ascites. Peritoneal metastasis of ovarian cancer is a major cause of the negative treatment outcome, as these metastases are resistant to most chemotherapy regimens. The aim of this study was to clarify aggressive pathology of peritoneal metastasis and examine the therapeutic efficacy of a liposomal agent in the model. METHODS: A human cancer cell line ES-2 of ovarian clear cell carcinoma, known as a chemotherapy-resistant cancer, was cultured in nonadherent plate to form spheroid and single cell suspension was transplanted into mouse peritoneal cavity. The epidermal growth factor receptor (EGFR) pathways in the cellular aggregates were analyzed both spheroid and ascites. The pharmacokinetics and therapeutic efficacy of CPT-11 (45 mg/kg) and IHL-305 (45 mg/kg), an irinotecan-encapsulated liposome, were examined by intravenous administration. RESULTS: Established peritoneal metastasis model showed an accumulation of ascites. The activation of EGFR and Akt was demonstrated in cellular aggregates both in the spheroid and ascites. In ascites samples, the area under the curve of SN-38, the activated form of CPT-11, was 3.8 times higher from IHL-305-treated mice than from CPT-11-treated mice. IHL-305 prolonged the survival time and decreased the accumulation of ascites and tumor metastasis. The median survival time were 22, 37 and 54 days in the control, CPT-11-treated, and IHL-305-treated mice, respectively. CONCLUSIONS: EGFR/Akt pathway contributes to the aggressive progression in ES-2 peritoneal metastasis model and effective delivery into ascites of IHL-305 was thought to useful treatment for ovarian cancer with peritoneal metastasis.